Fetal Thrombotic Vasculopathy: Significance in Liveborn Children Using Proposed Society for Pediatric Pathology Diagnostic Criteria. (February 2015) - Chisholm, Karen M.; Heerema-McKenney, Amy
Abstract : Fetal thrombotic vasculopathy (FTV) is a recently described placental diagnosis associated with adverse perinatal outcomes. The Society for Pediatric Pathology proposed criteria for grading; however, no study has evaluated the proposed thresholds or established standards for large-vessel lesions. Using the Society for Pediatric Pathology criteria of 2 or more foci of 15 or more avascular villi or villous stromal-vascular karyorrhexis to represent severe FTV, this study examines the outcomes of liveborn infants with placentas demonstrating severe or nonsevere distal villous FTV (DV-FTV) and large-vessel FTV (LV-FTV). Control placentas over the same 3-year period were selected with minimal findings. Electronic medical records were queried for birth data, infant laboratory values, morbidities, and neurological development. The 139 cases included 102 with DV-FTV and 94 with LV-FTV. Compared with 111 controls, the 52 severe DV-FTV cases were significantly associated with delivery for fetal indications and small placental weight. The children with severe DV-FTV were more likely to be born small for gestational age, have intracranial hemorrhage, coagulopathy, neurological impairment, growth retardation, and evidence of systemic thrombosis/vasculopathy. Compared with controls, the 67 cases with severe LV-FTV were associated with maternal preeclampsia, delivery for fetal indications, small placental weight, umbilical cord abnormalities, and small size per gestational age. The 45 cases of DV-FTV or LV-FTV not classified as severe had similar characteristics as those without any FTV. In conclusion, severe FTV does appear associated with neurological injury, whereas those with nonsevere lesions have similar rates of morbidities as controls. Abstract : Supplemental Digital Content is available in the text.